Relationship between pre-service teacher's epistemological beliefs and knowledge acquisition approaches - Abdullah, Maria Chong; Jikamshi, Mahmud Haruna; Roslan, Samsilah; Ismail, Habsah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study examines the relationship between dimensions of epistemological beliefs and knowledge acquisition approaches among pre-service teachers. In this quantitative study, a total of 418 pre-service teachers participated in the study comprising of, 215 males and 203 females, studying in colleges of education in Northern Nigeria. Pearson correlation was employed for data analysis of the study. The result showed that, there was a significant high and negative correlation between dimensions of epistemological beliefs and deep knowledge acquisition. However, the findings indicate a significant high positive correlation between the dimensions of epistemological beliefs and surface knowledge acquisition. Theoretical and practical implications of the study, as well as recommendations for future research, have been presented as well.